THEMATIC PROGRESSION IN STUDENTS’ HORTATORY EXPOSITION TEXTS - Suci Nur Asyifa Yuniawati; Sudarsono M. Ihrom; Fazri Nur Yusuf (Journal of English and Education, 2017)
This study focused on the investigation of theme and theme progression in students’ hortatory exposition text. This study employed a descriptive qualitative design. The data were twelve hortatory exposition texts written by eleventh grade students from one public school in Kabupaten Bandung. The texts were analysed by analysing the schematic structure and theme system derived from Systemic Functional Linguistics proposed by Halliday (1985). This study revealed that almost all the students’ texts had fulfilled its schematic structure of hortatory exposition text. In addition, students employed various textual strategies in organizing an exposition text as seen from the application of various theme choices such as marked and unmarked topical theme, interpersonal theme to make their texts coherent. In terms of theme progression, the students seemed to make the text clear and focus, so they manipulated the theme reiteration pattern dominantly. Based on the findings, it is recommended that theme and theme progression analysis can be applied in language studies to gain a better control of text organization and development. It is also suggested that further researcher can investigate the other texts or analyse the text beyond the theme system.